Pengaruh Model Project Based Learning Terhadap Kemampuan Berpikir Kreatif pada Pembelajaran IPAS Kelas IV SD Negeri 1 Sidokerto - Fauriza Agustina; Frida Destini; Agung Dian Putra; Rapani Rapani (Universitas Sebelas Maret, 2025)
This research identifies the problem of low creative thinking skills in class IV A SD Negeri 1 Sidokerto, which is caused by the lack of a variety of learning models that are applied optimally. This inhibits students in developing creativity. The purpose of this study was to determine the significant effect of applying the Project Based Learning model on creative thinking skills in IPAS learning and to determine the significant difference between the application of the model in experimental and control classes. This research used quantitative method with quasi experimental design and nonequivalent control group design model. The research sample consisted of 34 students. Data collection techniques included tests, observations, interviews, and documentation. The results showed a significant effect of applying the Project Based Learning model on creative thinking skills in IPAS learning, as indicated by the results of simple linear regression which resulted in a significance value of 0.002 <0.05, which means that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. The results of the independent sample t-test also show a significant difference between the experimental class and the control class, with a sig (2-tailed) value of 0.000 <0.05, which also leads to the rejection of Ho and acceptance of Ha.